Modeling the spatiotemporal urban spillover effect of high-speed rail infrastructure development - Satoshi Miyazawa; Jetpan Wetwitoo; K. E. Seetharam (Asian Development Bank Institute (ADBI), 2019)
The study introduces and applies the concept of spillover effects to high-speed rail development to formulate the economic impact on increasing the regional tax revenue. The previous study covered JR-Kyushu's development of the Kyushu Shinkansen (Kagoshima Route) in Kyushu region, Japan. The construction started in 1991, and it commenced operation in 2004 and became fully operational in 2011. This study aims to extend the idea to spatiotemporal modeling and analysis by developing a spillover effect extent estimation model. We use spatiotemporal land cover, land price panel, and municipality tax revenue data to conduct a preliminary analysis to understand the regional trend. The preliminary analysis suggests that the land price and the property tax revenue increased in the municipalities around high-speed rail stations during the construction period of the Kyushu Shinkansen. However, the trend around each station varied during the operation period. Our model takes those input data and estimates the spillover extent in a 1 km grid of land cover to highlight the characteristics of the spillover effect around each station. It optimizes the extent based on the compound annual growth rate in each target phase of high-speed rail (HSR) development. The result suggests that some of the features around stations promote the spillover effect while other features may obstruct it.
Keywords: O18; R4; R42; 330; high-speed rail; urban development; spillover effect extent estimation model